Maternal weight trajectories between early pregnancy and four and nine months postpartum. (June 2016) - Mullaney, L.; O'Higgins, A.C.; Cawley, S.; Daly, N.; McCartney, D.; Turner, M.J.
Highlights: Weight and BMI changes after pregnancy are not linear. Weight changes after pregnancy is different in obese compared with non-obese women. 16.6% normal BMI women in early pregnancy were overweight at four months postpartum. 11.1% normal BMI women in early pregnancy were overweight at nine months postpartum. 90% of those who were obese in early pregnancy were obese at four and nine months postpartum.